Biological samples for examination: concepts, conditions, sampling tactics (Bulletin of Kharkiv National University of Internal Affairs, 2024)
During the commission of crimes, traces of biological origin are left on the objects of the environment, tools, clothing, and the body of the participants. To conduct an identification study, an expert needs to compare the traces of the crime with biological samples of the person being tested. Criteria for determining biological samples are proposed. The biological criterion means that the samples reflect the internal and external properties of a person as a biological organism. The informational criterion is that the samples meet certain requirements: undoubted origin, required quantity, proper quality, compatibility with traces of crime. The identification criterion establishes that the human properties reflected by the samples are individual, stable, cannot be deliberately altered by a person and are suitable for identification. The procedural criterion means that biological samples must be collected in a lawful manner. Based on these criteria, biological samples for examination include: body parts; secretions as products of human activity; imprints of the skin relief of the human body.The mandatory participants in the collection of biological samples as a procedural action are: persons from whom biological samples are collected; officials who conduct the collection of samples and are responsible for its legality and validity; a specialist or expert; witnesses; employees of the relevant law enforcement agencies (in the case of compulsory collection of biological samples). Optional participants are a defence counsel, legal representative, representative, lawyer, doctor at their request.During the compulsory collection of biological samples, in order to ensure the legality, objectivity, reliability of the objects of expert research, preservation of health and observance of human rights, it is necessary to comply with legal, ethical, medical and forensic conditions. The author proposes a general algorithm for the tactics of obtaining biological samples for examination at the stage of pre-trial investigation, which includes the preparatory, working and final stages.
Keywords: criminal proceedings; forensic examination; biological samples; compulsory sampling; sampling conditions; sampling tactics.